Management of academic projects and behavioral skills in professional and technological education (Research, Society and Development, 2022)
Professional and technological education has the legal premise of linking theoretical and practical aspects and the importance of work as an educational basis, actively inserting the student in situations that require different skills. However, many of the projects developed in this educational modality contribute little to these aspects by not providing conditions for the development of these behavioral skills (soft-skills) that are important for the initiation, planning, execution, monitoring, control and closure of projects. Thus, this work aimed to insert managerial strategies based on the PMBOK guide for the development of completion works (TCCs) of a higher education course in technology. The elaboration of the TCCs began with a "Design thinking" session as a motivating dynamic and throughout the other stages there was a need to use tools such as SWOT analysis, Canvas business model, Kanban methodology, Gantt diagram, among others. In addition, there were verification steps through questionnaires that indicated the importance of educational projects when simulating situations of future professional practice and also positively and negatively related skills such as communication, flexibility, integrity, interpersonal skills, positive attitude, professionalism, responsibility, work in team, ethics and technical aptitude, through the analysis of clusters by similarity. Finally, the beneficial aspects of this strategy were highlighted, as it went beyond a mostly technical training, but integrated with professional and human development.